Recommendations for a doctor-patient communicating in oncology, obstetrics, gynecology and pediatrics - Trachuk, Lidia (Psychosomatic Medicine and General Practice, 2019)
Background: The quality and effectiveness of health care is largely determined by the quality of contact between doctor and patient. Possessing communicative skills and knowledge of effective means of medical communication allows a doctor of any specialty to solve more effectively complex tasks that arise in the medical-diagnostic process. Effective communication and strong patient–physician relationships, while central to all fields of medicine, are of particular importance in obstetrics and gynecology given the sensitive and intimate nature of commonly addressed clinical concerns. Communication between clinicians and patients is a multidimensional concept and involves the content of dialogue, the affective component (i.e., what happens emotionally to the physician and patient during the encounter), and nonverbal behaviors. Communicating with oncological, obstetric, gynecological and pediatric patients is a challenging task and requires considerable attention and communicative competence of doctors. Methods: This review is based on materials of the articles on the recommendations of evidence-based medicine concerning the communication of doctors and patients in oncology, obstetrics and gynecology and pediatrics clinics. Results: As a result, we anticipate that this review will distribute and promote knowledge about methods of evidence-based medicine for improving communication in obstetrics-gynecology, pediatrics and oncology clinics. Conclusion: The physicians’ ability to communicate effectively is the key to a successful relationship between a patient and a doctor. The current state of the health care system requires increased clinical efficacy and less time for each patient, which may impede the quality of communication between the patient and the physician. According to the American Academy of Pediatrics, effective communication is a cornerstone of care, an answer to the needs of the patient and the dynamics of the family. The use of a patient-centered approach, empathy, shared decision-making improves the relationship between patient and physician, the effectiveness of therapy and increased adherence to prescribed treatment in oncology, obstetrics, gynecology and pediatrics.